Sustainability and meat consumption: is reduction realistic? - Jantine Voordouw; Hans Dagevos (Sustainability: Science, Practice, & Policy, 2013)
Meat is critical with respect to sustainability because meat products are among the most energy-intensive and ecologically burdensome foods. Empirical studies of the meat-consumption frequency of Dutch consumers show that, apart from meat-avoiders and meat-eaters, many people are meat-reducers that eat no meat at least one day per week. Meat-consumption frequencies provide empirical evidence for different modes of “flexitarianism,” including light, medium, and heavy flexitarians. In particular, the existence of heavy flexitarians suggests that the customary position of meat and other animal-based dietary products in the food hierarchy is not inviolable. To improve our understanding of meat reduction, cluster analysis adds information about differences across flexitarians. Given the enormous environmental impact of animal-protein consumption and the apparent sympathy of consumers for meat reduction, it is surprising that politicians and policy makers demonstrate little, if any, interest in strategies to reduce meat consumption and to encourage more sustainable eating practices.